4000 Years of Migration and Cultural Exchange The Archaeology of the Batanes Islands, Northern Philippines - Bellwood, Peter (Terra Australis, 2013)
The project reported on in this monograph has been concerned with the archaeology of the Batanes Islands, an archipelago that must have been settled quite early in the process of Austronesian dispersal from Taiwan southwards into the Philippines. A multi-phase archaeological sequence covering the past 4000 years for the islands of Itbayat, Batan, Sabtang and Siayan is presented, extending from the Neolithic to the final phase of Batanes prehistory, just prior to the late 17th century arrivals of foreign navigators such as Jirobei (Japan) and William Dampier (England), followed by the first Spanish missionaries. So far, no traces of preceramic settlement have been found in Batanes, but the archaeological sequence there from the Neolithic onwards, like that in the Cagayan Valley in northern Luzon, is now one of the best-established in the Philippines.